Behavior of eco-friendly concrete reinforced with hybrid recycled fibers - Radwa Defalla Abdel Hafez1; Raghda Osama Abd-Al Ftah; Bassam Abdelsalam Abdelsalam; Ibrahim Saad Agwa (Sustainable Structures)
Recycling waste materials is a crucial strategy to reduce landfill disposal. The emission of greenhouse gases like methane and carbon dioxide into the atmosphere by landfills is well-known to be harmful to both people and the environment. Urgent action is required to address the pressing social and environmental issue of how to dispose of used tires. This study aimed to develop an eco-friendly concrete (EFC) mix that uses recycled aluminum cans and tire wire as reinforcement. Examine how EFC's workability and mechanical qualities are impacted by recycled fibers as well. Ten concrete mixes were experimented with in this research and divided into three groups. Three mixes contain 0.5%, 1%, and 2% of the aluminum can fibers (ACF), and three mixes include 0.5%, 1%, and 2% of tire wire fibers (TWF), three mixtures incorporate 0.5%, 1%, and 2% of hybrid recycled fibers (HRF) of both ACF and TWF, in addition, control mix. The workability and mechanical tests of eco-friendly concrete were investigated. The experimental results show that the recycled fiber volume fractions (RFVFs) are inversely proportional to the concrete workability. The recycled fibers don’t reveal any significant effects on the compressive strength and the elastic modulus of concrete. All recycled fiber ratios improved the concrete behavior for tensile and flexural resistance. The development ratio of concrete mix containing 1% TWF reached 53.2% and 62.4% for tensile and flexural strengths, respectively. It can be noticed that the recycled fibers are enhancing the failure of the concrete matrix to become ductile failure rather than brittle behavior. However, the recycled fibers have arrested the development of cracks in the internal concrete structure.